Navigating Discourse through Controversy in the Classroom - Scott, John (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2023)
Social studies is an evolving subject that encompasses controversial issues including abortion, gun control, substance legalization, LGBTQ, civil rights issues, and more. To elevate discourse, teachers have a myriad of ways to elicit thought-provoking discussions among students. Strategies for discussing controversial issues include creating a positive environment where students do not feel judged for expressing their views, cooperative learning, reciprocal teaching, debate, and discussion. Cooperative learning forces individuals to respect the viewpoint and work habits of classmates. Debate and discussion are also effective discourse methods because students must accurately represent positions on issues. This is done through research of reputable sources guided by teacher instruction and moderation to facilitate an inclusive and productive discussion. Instruction and moderation are demonstrated below.